Vessel grafts for tissue engineering revisited—Vessel segments show location‐specific vascularization patterns in ex vivo ring assay. (10th December 2021) - Vaghela, Ravikumar; Arkudas, Andreas; Steiner, Dominik; Heltmann‐Meyer, Stefanie; Horch, Raymund E.; Hessenauer, Maximilian
Abstract: Objective: Transplantation of prefabricated tissue‐engineered flaps can be a potential alternative for healing large tissue defects. Providing adequate vascular supply for an engineered tissue construct is one of the key points in establishing successful tissue engineering‐based treatment approaches. In tissue engineering‐based vascularization techniques like the arteriovenous loop, vascular grafts with high angiogenic potential can help to enhance neovascularization and tissue formation. Therefore, our study aimed to compare the angiogenic potential of vascular grafts from different locations in the rat. Methods: The angiogenic activity was investigated by an ex vivo vessel outgrowth ring assay using 1‐mm height vascular segments embedded in fibrin for 2 weeks. Results: Maximum vessel outgrowth was observed on Days 10–12. Upper extremity vessels exhibited stronger outgrowth than lower extremity vessels. Moreover, arterial vessels demonstrated higher angiogenic potential compared with venous vessels. Conclusion: Collectively, our ex vivo findings suggest that upper extremity arterial vessels have a higher angiogenic capacity, which could be used to improve neovascularization and tissue formation in tissue engineering.